Clinical utility of robot-assisted transthoracic esophagectomy in advanced esophageal cancer after neoadjuvant chemoradiation therapy - Yun, Jae Kwang; Lee, In-Seob; Gong, Chung-Sik; Kim, Bum Soo; Kim, Hyeong Ryul; Kim, Dong Kwan; Park, Seung-Il; Kim, Yong-Hee (Journal of Thoracic Disease, 2019)
Background: Although robot-assisted minimally-invasive esophagectomy (RAMIE) surgeries are expanding clinically, few studies have reported patients with locally-advanced esophageal cancer who underwent neoadjuvant chemoradiation therapy (nCRT). Methods: From 2013 to 2017, 219 patients with esophageal squamous cell carcinoma underwent RAMIE and 35 of them received nCRT at our institution. During the period, 289 patients underwent conventional open esophagectomy (OE) and 111 patients underwent nCRT. We compared postoperative mortality and morbidity of RAMIE and OE patients after nCRT. Results: In patients who received nCRT, the RAMIE and OE groups had similar operative time, estimated blood loss, early-period mortality, and recurrence rate (≤1 year) and both groups showed a high rate of complete resection. With respect to postoperative morbidities, such as anastomotic leakage, chylothorax, postoperative bleeding, and wound infection, only vasopressor use was significantly higher in the OE group (P